2005
DOI: 10.1152/ajpregu.00556.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cortisol on cardiac myocytes and on expression of cardiac genes in fetal sheep

Abstract: In 17 fetal sheep aged 129 days, the effects of large-dose infusions of cortisol (72.1 mg/day for 2-3 days) on proliferation, binucleation, and hypertrophy of cardiac myocytes, cardiac expression of angiotensinogen, angiotensin receptor subtypes 1 and 2, Glut-1, glucocorticoid and mineralocorticoid receptors, proteins of the MAPK pathways and calcineurin were studied. Cortisol levels were 8.7 +/- 2.3 nM (SE) in 8 control and 1,028 +/- 189 nM in 9 treated fetuses (P < 0.001). Cortisol had no effect on myocyte b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 33 publications
3
89
2
Order By: Relevance
“…The fetal blood pressures from that study were not reported. In a study by Lumbers et al (2005) high dose infusion of cortisol (72 . 1 mg/d for w60 h) increased LV myocyte size and increase cardiac angiotensinogen mRNA, suggesting an induction of hypertrophy.…”
Section: Mechanisms Of Enlargement Of the Fetal Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…The fetal blood pressures from that study were not reported. In a study by Lumbers et al (2005) high dose infusion of cortisol (72 . 1 mg/d for w60 h) increased LV myocyte size and increase cardiac angiotensinogen mRNA, suggesting an induction of hypertrophy.…”
Section: Mechanisms Of Enlargement Of the Fetal Heartmentioning
confidence: 99%
“…Giraud et al (2006) have shown that cortisol chronically infused directly into the coronary artery increased cell cycle activity in myocytes of late gestation sheep fetuses, suggesting a direct induction by cortisol of hyperplastic growth rather than hypertrophic growth. Conversely, it has been demonstrated that large doses of cortisol infused directly into the fetus in late gestation causes left ventricular (LV) hypertrophy along with an increase in fetal arterial pressure and cardiac expression of angiotensinogen mRNA (Lumbers et al 2005). We have shown that maternal cortisol infusion in sheep during late gestation caused an increase in fetal heart size and wall thickness without increasing fetal arterial pressure or cardiac angiotensinogen; we found an increase in the ratio of angiotensin type 2 receptor (AT2 receptor) to AT1 receptor mRNA in the fetal heart, suggesting that the renin-angiotensin system (RAS) may play a key role in the enlargement process.…”
Section: Introductionmentioning
confidence: 99%
“…is associated with abnormal heart growth and other cardiovascular diseases (Souverein et al, 2004). In mammalian experimental models, glucocorticoids like cortisol directly induce cardiomyocyte hypertrophy in vitro (Whitehurst et al, 1999;Ren et al, 2012) and in vivo (Clark et al, 1982;de Vries et al, 2002;Jensen et al, 2002;Lumbers et al, 2005), indicating a direct role of cortisol in heart remodelling, growth and disease.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to mammals, where aldosterone is an important hormone in myocardial remodeling (Funder, 2001;Rocha et al, 2002;Qin et al, 2003), most teleosts, including salmonids, do not produce aldosterone (Bern, 1967;Sangalang and Uthe, 1994), and mineralcorticoid functions are instead mediated by cortisol (Bern and Madsen, 1992;Wendelaar Bonga, 1997). Furthermore, in mammals, glucocorticoids like cortisol directly induce protein synthesis and hypertrophy of cardiomyocytes in vivo and in vitro (Nichols et al, 1984;Lumbers et al, 2005), and plasma cortisol levels have been found to represent an independent risk factor of cardiac events and death (Yamaji et al, 2009). Accordingly, to examine the effect of stress and cortisol on myocardial morphology and function, we examined cardiac structure and gene expression in the hearts of two genetically distinct strains of rainbow trout (Oncorhynchus mykiss Walbaum 1792) that respond to stress with either a high [high responsive (HR)] or low [low responsive (LR)] cortisol production (Pottinger and Carrick, 1999).…”
Section: Introductionmentioning
confidence: 99%